KLASIFIKASI KUALITAS PERMUKIMAN MENGGUNAKAN CITRA QUICKBIRD DI KECAMATAN MANDIANGIN KOTO SELAYAN KOTA BUKITTINGGI - Sri Bening Pratiwi; Triyatno Triyatno; Fitriana Syahar (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
ABSTRACT The purpose of this research are (1) describe the quality parameters of settlement, (2) analyze the distribution of quality of settlements, (3) test the accuracy of interpretation Quickbird. Methods used for the quality of settlements is scoring and overlay. Accuracy of interpretation used confusion matrix method. Based on research result show that (1) the quality parameter of the settlements is the density of the settlements has a medium quality of 120 Ha, the pattern of the building layout has a bad quality of 182 Ha, tree protective settlement has a bad quality of 233 Ha, the road width has bad quality the extent of 207 Ha, the condition of residential road has good quality which is 204 Ha, and the residential location variable has medium quality which is 91 Ha. (2) the distribution of settlement quality in the subdistric Mandiangin Koto Selayan for the medium quality of settlements are having an area of 125 Ha, the quality of bad settlements has an area of 118 Ha. The medium quality of the settlements is the most in the village Kubu Gulai Bancah while the bad quality is the most in the village Campago Guguak Bulek. (3) test image accuracy using confution matrix produce accuracy of image that is 94,73%.